ONLINE CSR BUSINESS MODEL AS VALUE CREATION FOR PT MAP TBK - Prisca Sulaiman; Paskah Widarani; Matius Alvin; Jerry S. Justianto (Journal of Business Strategy and Execution, 2014)
In recent time the pressure on companies from governments, people and media on taking its social responsibility has increased. This created a trend of Corporate Social Responsibility, which is CSR as Value Creation. But some critics argue that CSR distracts from the economic role of businesses. In certain culture giving out or sharing to the less fortunate people will get back to us in form of blessings and luck. Regarding donation program, a new question arises from the people. Question about where is the money go and who had had my help or even trust issue about whether the donation is managed in transparent and in honesty. The purpose of this paper which named the program Affect.Action is to create business model as non-profit organization for MAP (PT Mitra Adi Perkasa) to manage its CSR and for the public so they can donate effortlessly using online platform. As CSR from MAP Affect.Action operational cost will be funded by MAP so that 100% of the donated fund will delivered for the development of the education sector. In Affect.Action we invite the public to participate from the beginning of the donation process to create emotional attachment. The people can choose the intended donation target every event in quarterly period and a  follow up story and audited report will be presented for public eyes after the donation has been delivered. They can even suggest the donation recipients to Affect.Action for further investigation. In return for their participation, MAP will gives several benefits as a gratitude.